PPS/PPC II: pretérito perfecto simple y pretérito perfecto compuesto en el español europeo - Azpiazu Torres, Susana; Gómez Asencio, José J.; Quijada Van Den Berghe, Carmen (Anales de Lingüística, 2020)
-